Cool Little Kids translational trial to prevent internalising: two‐year outcomes and prediction of parent engagement. Issue 3 (16th August 2020) - Bayer, Jordana K.; Prendergast, Luke A.; Brown, Amy; Harris, Lana; Bretherton, Lesley; Hiscock, Harriet; Beatson, Ruth; Mihalopoulos, Cathrine; Rapee, Ronald M.
Abstract : Background: The aim was to determine outcomes in the first year of school of a population‐delivered parenting program to prevent internalising problems in temperamentally inhibited preschool children and predictors of engagement in parenting groups. Method: Design : Randomised controlled trial. Setting : 307 preschool services across eight socio‐economically diverse government areas in Melbourne, Australia. Participants : 545 parents of inhibited 4‐year‐old children; 469 (86%) retained at two‐year follow‐up. Intervention : Cool Little Kids program. Primary outcomes were child internalising symptoms and anxiety disorders. Secondary outcomes were parenting, parent well‐being and engagement. Trial registration ISRCTN30996662 http://www.isrctn.com/ISRCTN30996662 . Results: In the first year of school ( M ( SD ) age 6.7 (0.4) years), child anxiety symptoms were reduced in the intervention versus control arm (PAS‐R M ( SD ): total 36.2 (17.2) versus 39.4 (18.5); adjusted difference −3.26, 95% CI −6.46 to −0.05, p  = .047; specific fears 9.1 (6.2) versus 10.7 (6.8), adjusted difference −1.53; 95% CI −2.69 to −0.38, p  = .009). However, there was little difference in broader child internalising (CMFWQ M ( SD ): 2.2 (0.5) versus 2.3 (0.6); adjusted difference −0.03, 95% CI −0.13 to 0.06, p  = .489) or anxiety disorders (37.6% vs. 42.6%; adjusted OR 0.79, 95% CI 0.53 to 1.18, p  = .242). Lower income, younger mothers, less educated and more culturally diverse fathers engaged less with the intervention. Continued skills practice was less frequent for parents of girls and in advantaged neighbourhoods. Conclusions: There were population effects of Cool Little Kids in the first year of school for anxiety symptoms but not disorders. Considering motivation techniques to engage subgroups of families would be helpful in translation research.